Up until the consolidation on the IFRS Foundation: The companies that have been advancing integrated reporting - Lopes, A. I.; Bovane, S.; Penela, D. (International Journal of Accounting, Auditing and Performance Evaluation, 2023)
This study seeks to develop an in-depth understanding of where companies reporting under the Integrated Reporting (IR) framework are located, what their main characteristics are, whether a change in firm value has occurred after IR adoption, and whether firm value varies depending on IR quality. Knowing who has been involved in the thinking and processes underpinning IR may further encourage companies to proceed, under the direction of the IFRS Foundation, with future practices associated with non-financial reporting. The results of this study show that IR reporters are distributed across 43 countries and five regions the majority from South Africa, followed by Japan and the UK. After adoption, IR reporters are found to be significantly larger, less profitable, and command greater market value. Those with higher-quality IR reporting are significantly larger and more profitable than their counterparts. Yet, no significant differences in firm value were found between IR quality groups.